Determinan Faktor Risiko Terjadinya Kanker Serviks - Zuhratul Aini; Suseno, Mutiara Rachmawati; Ni Putu Dian Ayu Anggraeni (Indonesian Health Issue, 2025)
Background : The cervix is influenced by various factors, including age, socio-economic status, age at first sexual intercourse, multiple sexual partners, uncircumcised sexual partners, parity, lack of maintaining genital hygiene, smoking, obesity, history of venereal disease, and family history of sufferers. Cervical cancer, chronic trauma to the cervix, use of sanitary napkins and pantyliners, diethylstilbestrol (DES), and use of oral contraceptives. Objective: To determine the determinants of risk factors for cervical cancer in the NTB Provincial Regional Hospital in 2023. Method: This type of research is observational analytic with a case-control research design. The sample was 156 people, consisting of 78 cervical cancer groups and 78 control groups. Data analysis used the Chi-Square test and logistic regression. Results: The results of the characteristics of the largest number there is a significant relationship between age of menarche (ρ value = 0.022), number of parities (ρ value = 0.000), use of hormonal contraception (ρ value = 0.000) nutritional status (ρ value = 0.000), number of marriages (ρ value = 0.000) and age at marriage (ρ value = 0.000) with the incidence of cervical cancer. Meanwhile, there was no significant relationship between smoking history (p value 0.586) and family history (p value 0.325) on the incidence of cervical cancer. And from statistical analysis using logistic regression, it was found that age at marriage is the dominant factor causing cervical cancer with an odd ratio value / Exp B = 3,773, meaning that people who have been married < 20 years have a 3,773 times greater risk of developing cervical cancer than people who have been married > 20 years. Conclusion: The results of statistical analysis show that age at menarche, number of parities, use of hormonal contraception, nutritional status, number of marriages, age at marriage play an essential role in increasing the risk of developing cervical cancer, while smoking habits and family history of cancer are not risk factors for cervical cancer, and Age at marriage is the dominant factor causing cervical cancer in NTB Provincial Regional Hospital in 2023. Suggestion: There is a need to develop community-based intervention models to increase awareness and compliance with screening.